Trends and factors associated with tuberculosis-related mortality during the intensive phase of anti-tuberculosis treatment in Johor from 2013 to 2022 - Ramlan, Dzul Hairy Mohd (2024)
Background: Tuberculosis (TB) remains a major global health challenge. In Malaysia, recent TB data reveal a significant deviation from the targets set by the End TB Strategy, with a 28% increase in TB fatalities in 2022 compared to 2021. Despite extensive TB control efforts, Johor state has witnessed fluctuating mortality rates during the intensive phase (IP) of anti-TB treatment, underscoring the need for an in-depth analysis of associated factors. Objective: This study aimed to describe the proportion and trends of TB-related mortality and its associated factors during the IP of anti-TB treatment in Johor from 2013 to 2022. Methods: A case-control study was conducted in January 2024 until the end of May 2024 using secondary data from the MyTB system. The proportion of TB-related mortality and total of TB cases were calculated based on the data extracted from MyTB system with no sampling method applied, A case (n=372) consists of a TB patient who dies due to TB during the IP and the the control group (n=1671) was randomly selected from TB cases who survived during the IP. Descriptive statistics and logistic regressions were employed for data analysis using SPSS version 29. Results: The proportion of TB-related deaths during the intensive phase (IP)IP in Johor from 2013 to 2022 ranged between 0.8% and 3.6%, with 2022 having the highest rate. Of the 2,043 participants, the average age was 49.2 years for cases and 42.5 years for controls. Most were male (76.3%), Malaysian (89.5%), from urban areas (65.1%), HIV-negative (81.5%), had received BCG vaccination (86.8%), were new TB cases (92.2%), had positive sputum AFB (79.3%), were initially treated at government hospitals (88.4%), and did not adhere to DOTS (80.1%). The significant independent risk factors for TB-related mortality during IP were being older than 65 years (AOR: 10.14; 95% CI: 1.27, 80.7; p=0.029), living in an urban area (AOR: 0.55; 95% CI: 0.35, 0.86; p=0.008), HIV-positive (AOR: 2.95; 95% CI: 1.53, 5.69; p=0.001), AFB positive (AOR: 2.42; 95% CI: 1.43, 4.10); p=0.001), far-advanced lesions on chest radiograph (AOR: 14.53; 95% CI: 7.12, 29.64; p<0.001), initiating treatment at a government hospital (AOR: 5.73; 95% CI: 2.07, 15.86; p<0.001), and adherence to DOTS (AOR: 0.009; 95% CI: 0.006, 0.015; p<0.001).[d2][NN3] Conclusion: This study highlights fluctuating trends in TB-related mortality during the IP, with a notable peak in 2022. Public health strategies should focus on early detection, integrated TB-HIV care, and strict adherence to DOTS, particularly for high-risk populations. In line with the National TB End Strategy, these findings are crucial for guiding future interventions and policies aimed at reducing TB mortality rates and improving treatment outcomes in Johor and similar settings.